Multisite interactions of prions with membranes and native nanodiscs. (May 2021) - Overduin, Michael; Wille, Holger; Westaway, David
Highlights: Prions are shown to be membrane-dependent rather than prion-only particles. Native lipid interactions are revealed using native nanodiscs known as SMALPs. A structured binding site for membrane recognition is discovered using MODA. The plethora of lipid binding elements are modulated by disease-linked mutations. Conversion alters and propagation reinforces the membrane interaction surface. Abstract: Although prions are known as protein-only infectious particles, they exhibit lipid specificities, cofactor dependencies and membrane-dependent activities. Such membrane interactions play key roles in how prions are processed, presented and regulated, and hence have significant functional consequences. The expansive literature related to prion protein interactions with lipids and native nanodiscs is discussed, and provides a unique opportunity to re-evaluate the molecular composition and mechanisms of its infectious and cellular states. A family of crystal and solution structures of prions are analyzed here for the first time using the membrane optimal docking area (MODA) program, revealling the presence of structured binding elements that could mediate specific lipid recognition. A set of motifs centerred around W99, L125, Y169 and Y226 are consistently predicted as being membrane interactive and form an exposed surface which includes α helical, β strand and loop elements involving the prion protein (PrP) structural domain, while the scrapie form is radically different and doubles the size of the membrane interactive site into an extensible surface. These motifs are highly conserved throughout mammalian evolution, suggesting that prions have long been intrinsically attached to membranes at central and N- and C-terminal points, providing several opportunities for stable and specific bilayer interactions as well as multiple complexed orientations. Resistance or susceptibility to prion disease correlates with increased or decreased membrane binding propensity by mutant forms, respectively, indicating a protective role by lipids. The various prion states found in vivo are increasingly resolvable using native nanodiscs formed by styrene maleic acid (SMA) and stilbene maleic acid (STMA) copolymers rather than classical detergents, allowing the endogenous states to be tackled. These copolymers spontaneously fragment intact membranes into water-soluble discs holding a section of native bilayer, and can accommodate prion multimers and mini-fibrils. Such nanodiscs have also proven useful for understanding how β amyloid and α synuclein proteins contribute to Alzheimer's and Parkinson's diseases, providing further biomedical applications. Structural and functional insights of such proteins in styrene maleic acid lipid particles (SMALPs) can be resolved at high resolution by methods including cryo-electron microscopy (cEM), motivating continued progress in polymer design to resolve biological and pathological mechanisms.